Pediatric and Congenital Cardiology, Cardiac Surgery and Intensive Care - Da Cruz, Eduardo M.; Ivy, Dunbar; Jaggers, James (Springer London : Imprint: Springer, 2014)
Pediatric and Congenital Cardiology, Cardiac Surgery and Intensive Care provides a consistent and comprehensive approach to multiple congenital and acquired cardiac pathologies pre, peri and postoperatively, with the use of algorhythms, guidelines and current research issues. Included with the e-reference are interactive videos with the most common interventions, online access to practical learning activities, and to the comprehensive Aristotle score and database. This reference work satisfies the need for a universal and practical review of management of critically ill children and adults with congenital heart disease, based upon taskforce decisions and the cumulative experience of the world leaders in the field.